3=2x-y=0 -3-7y=10x solve for x and y by useing process of elimination
in Algebra 2 Answers by

Your answer

Your name to display (optional):
Privacy: Your email address will only be used for sending these notifications.
Anti-spam verification:
To avoid this verification in future, please log in or register.

1 Answer

If you mean 3 + 2x - y = 0 then:

2x - y = -3

10x + 7y = -3

multiply the top equation by 7 on both sides

14x - 7y = -21

10x + 7y = -3

add the bottom equation to the top

24x + 0y = -24

10x + 7y = -3

divide the top by 24 on both sides

x + 0y = -1

10x + 7y = -3

Now we know x = -1

multiply the top equation by -10

-10x + 0y = 10

10x + 7y = -3

add the top equation to the bottom

-10x + 0y = 10

0x + 7y = 7

divide the bottom equation by 7 on both sides

-10x + 0y = 10

0x + y = 1

Now we know y = 1

Answer:  x = -1, y = 1
by Top Rated User (103k points)

Related questions

Welcome to MathHomeworkAnswers.org, where students, teachers and math enthusiasts can ask and answer any math question. Get help and answers to any math problem including algebra, trigonometry, geometry, calculus, trigonometry, fractions, solving expression, simplifying expressions and more. Get answers to math questions. Help is always 100% free!
85,985 questions
91,877 answers
2,227 comments
23,904 users